The Fundamental Concepts of High SMAS Facelift: Literature Review - Gede Wara Samsarga; I Made Suka Adnyana; Astrinita Lestari Suyata; Shita Diwyani Sudarsa; Dewa Ayu Agung Anggita Ningrat (DiscoverSys Inc., 2022)
A number of facelift procedures have been introduced by many surgeons but there is no consensus has yet been established to carry. Since the first description of superficial musculoaponeurotic system (SMAS), it is used as the basis for many facelift methods that produce superior result in rejuvenation compared to traditional skin only facelift. Extended SMAS facelift becoming SMAS modification techniques that is still being developed. It produces two different vector of subcutaneous and SMAS flap, that is essential to restore drooping deep facial tissue with natural appearance. Despite the beneficial use of extended SMAS flap, most of plastic surgeons still traditionally incise the SMAS under the zygomatic arch. However, the low SMAS incision results only on rejuvenation of the lower face and is not sufficient to correct mid-facial aging. Fundamental concepts of high SMAS facelift by reviewing some literatures explain that high SMAS flap transection allowing the surgeon to achieve greater vertical elevation of the deep structures of the face by undermining the middle face, combined with fixation to a fixed structure produces lasting results and oblique vector of skin envelope creating no tension look. Incision above zygomatic arch turns out to be safely performed without facial nerve injury thorough knowledge of the anatomy. The final result is a balanced and harmonious elevation of sagging tissues of the midface, cheek, and jawline, to such an extent that high SMAS facelift becomes optimal, durable, technically simple, reproducible and with a comparatively high safety margin in facelift procedures.